Dual Inhibition of Activin/Nodal/TGF-β and BMP Signaling Pathways by SB431542 and Dorsomorphin Induces Neuronal Differentiation of Human Adipose Derived Stem Cells - Vedavathi Madhu; Abhijit S. Dighe; Quanjun Cui; D. Nicole Deal (Stem Cells International)
Damage to the nervous system can cause devastating diseases or musculoskeletal dysfunctions and transplantation of progenitor stem cells can be an excellent treatment option in this regard. Preclinical studies demonstrate that untreated stem cells, unlike stem cells activated to differentiate into neuronal lineage, do not survive in the neuronal tissues. Conventional methods of inducing neuronal differentiation of stem cells are complex and expensive. We therefore sought to determine if a simple, one-step, and cost effective method, previously reported to induce neuronal differentiation of embryonic stem cells and induced-pluripotent stem cells, can be applied to adult stem cells. Indeed, dual inhibition of activin/nodal/TGF-β and BMP pathways using SB431542 and dorsomorphin, respectively, induced neuronal differentiation of human adipose derived stem cells (hADSCs) as evidenced by formation of neurite extensions, protein expression of neuron-specific gamma enolase, and mRNA expression of neuron-specific transcription factors Sox1 and Pax6 and matured neuronal marker NF200. This process correlated with enhanced phosphorylation of p38, Erk1/2, PI3K, and Akt1/3. Additionally, in vitro subcutaneous implants of SB431542 and dorsomorphin treated hADSCs displayed significantly higher expression of active-axonal-growth-specific marker GAP43. Our data offers novel insights into cell-based therapies for the nervous system repair.